Peningkatan Hasil Belajar Informatika Peserta Didik Kelas VII-3 Menggunakan Model Problem Based Learning Berbantuan Quizziz - Mayta Prasasti, Francisca Anindya; Azhar Ahmad Smaragdina; Friday Okti Venanda Mega Pratami; Dion Dwi Rizky (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The research in the following research aims to determine the effect of the application of the Problem Based Learning (PBL) model assisted by Quizizz media on improving the learning outcomes of class VII-3 students in informatics subjects. A quantitative approach with a quasi-experimental design of the nonequivalent control group design type was used in this study. The sample consisted of 32 class VII-3 students, divided into an experimental group (15 students) and a control group (15 students). Data were collected through learning outcome tests and observations, then analyzed using normality tests, homogeneity tests, and t-tests. The results showed a sig. (2-tailed) value of 0.001, smaller than 0.05, so Ha was accepted and Ho was rejected, indicating a significant effect of the PBL model assisted by Quizizz on student learning outcomes. This approach provides meaning to the urgency of increasing student involvement, learning motivation, and conceptual understanding through real-world problem solving and interactive evaluation.